FORMS OF STATE POLICY IMPLEMENTATION IN THE SPHERE OF STATE SUPPORT OF LOCAL GOVERNMENT IN UKRAINE - Tkachenko, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose: to clarify the meaning of the concept of "forms of implementation of the function of state policy in the sphere of state support of local self-government" in Ukraine, to substantiate methodological approaches to their scientific knowledge and ways of improving the mechanism of state support of local self-government. Results: the content of the category "forms of implementation of the function of state support of local self-government" was disclosed and their classification was carried out in relation to the forms of implementation of state functions. It is substantiated, that the approaches to understanding the concept of the forms of implementation of state functions and their systematization formulated in the general theory of the state and law, fully apply to the forms of implementation of the function of state support of local self-government in Ukraine. Based on this, the concept of the form of implementation of the function of state support of local self-government was formulated, their systematization was carried out, and the peculiarities of legal and non-legal (organizational) forms of implementation of the corresponding state function were determined. Discussion: in modern scientific developments, the form of implementation of the function of state support of local self-government was not specifically considered or was considered, for the most part, fragmentarily, as a result of which this issue remains insufficiently researched.